The Aesthetics of Deformity and the Construction of the "Freak". Issue 2 (1st June 2020) - Backe, Emma Louise
Abstract: With the inception of the "freak show" in the late 19 th and early 20 th centuries, deformity, physical abnormality and unusual facial features were sensationalized into entertainment spectacle, covertly managed, constructed and displayed for the macabre amusement of sideshow visitors and audience members. Due to the historical manipulation and fabrication of freaks' bodies by sideshow and Odditorium managers to heighten or diminish their "freakish" qualities, the freak show can be conceptualized as an aesthetic space. By framing these social events as an aesthetic space, it is possible to analyze and deconstruct these bodies in the same way a work of art is appraised and valued. A freak is made, rather than born, and the physical elements that constitute freakishness are entirely dependent on the cultural norms and values of the time. Thus the cultural category of a freak is both historically and socially contingent. Through this aesthetic lens, I examine the visual culture of freak shows in order to interrogate the methods of representation employed by sideshow managers. These methods neither disrupted nor subverted the culturally coded conceptions of normality or deformity but, rather, reinforced them. Managers utilized exoticism or aggrandizement, falsified life‐story pamphlets and visual chicanery to deliberately separate the audience from the freaks as objects of amusement and maintain social hierarchy. As the nineteenth century wore on, however, freak shows lost their cultural currency, which can be seen as the result of developing anthropological theory and medicine where spectators began to pathologize the deformed body.